Protected Culture for Vegetable and Small Fruit Crops: Types of Structures - Bielinski M. Santos; Gary Vallad; Emmanuel A. Torres-Quezada (EDIS)
A protective structure is defined as any structure designed to modify the environment in which plants are grown. Protective structures, such as greenhouses, screen houses, and tunnels, are known worldwide as production systems for high-quality vegetable and fruit crops. This 4-page fact sheet was written by Bielinski M. Santos, Gary Vallad, and Emmanuel A. Torres-Quezada, and published by the UF Department of Horticultural Sciences, July 2013.